EVALUASI KEGIATAN SOSIALISASI DAN PELEMBAGAAN ANALISIS SOSIAL EKONOMI DAN GENDER (SAGA) DALAM LITKAJI LINGKUP LITBANG PERTANIAN - RITA NUR SUHAETI; EDI BASUNO (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2004)
Evaluation on SAGA activity in Research and Assessment within the IAARD.Relatively low technology adoption level by end users had triggered application ofparticipatory approach, user oriented technology and more pay attention to user’s socialaspects. Socio-economic And Gender Analysis (SAGA) Core Team (SCT) establishment wasthe initiation of Socialization and Institutionalization program within the Indonesian Agencyfor Agricultural Research and Development (IAARD). The main objective of the program isto establish SAGA capacity of the researchers and extension workers within the IAARD. Thedata were gained from eight Assessment Institute for Agricultural Technology (AIAT) byapplying structured and semi-structured interviews and Focused Group Discussion (FGD).Respondents for the study were alumnae of the SAGA training workshop. The cascadetraining workshops were held within the period of 2000 - 2002, beginning from Training ofMaster Trainers (TOM), Training of Trainers (TOT) and Training of Staff (TOS). Number ofthe TOM, TOT and TOS were 18; 124; and 416 persons respectively. From the quantityaspect, the number seemed to be promising but not from the quality aspect. The cascadetraining has not given yet expected result. Each alumna was expected to be SAGA focalpoints and could establish networking within the region. The main cause was that not allalumnae could disseminate the SAGA approach in each working unit. Less optimal output ofthe TOM alumnae caused a bumpy regional networking establishment. This reflected thatTOM’s alumnae dependency level to the SCT was quite high. It also affected outputs of TOTand TOS. In addition, less understanding on SAGA materials of the respective facilitators ineach workshop ended in less understanding of the workshop participants. Various reportedresults of monitoring and evaluation (Monev) activities showed that the institutionalization ofSAGA approach was less optimal and it was reflected by low Monev grade of each observedAIATs.